2018
DOI: 10.1007/s10916-018-0991-9
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection for Automatic Tuberculosis Screening in Frontal Chest Radiographs

Abstract: To detect pulmonary abnormalities such as Tuberculosis (TB), an automatic analysis and classification of chest radiographs can be used as a reliable alternative to more sophisticated and technologically demanding methods (e.g. culture or sputum smear analysis). In target areas like Kenya TB is highly prevalent and often co-occurring with HIV combined with low resources and limited medical assistance. In these regions an automatic screening system can provide a cost-effective solution for a large rural populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…The experimental results validate the fine performance of X-RayNet for lung segmentation, which will be used for diagnostic purposes. [64] and [65] are taken from [2]. ACC means accuracy, J shows jaccard, and D means dice score.…”
Section: Lung Segmentation With Other Open Datasets Using X-raynetmentioning
confidence: 99%
“…The experimental results validate the fine performance of X-RayNet for lung segmentation, which will be used for diagnostic purposes. [64] and [65] are taken from [2]. ACC means accuracy, J shows jaccard, and D means dice score.…”
Section: Lung Segmentation With Other Open Datasets Using X-raynetmentioning
confidence: 99%
“…Similar experiments have also been demonstrated in [22], which focuses on the importance of transfer learning for medical image classifications, in the context of COVID-19. On the whole, researchers found that the use of chest radiographs is better in terms of lung abnormalities screening [11,14,[23][24][25][26]. With these, COVID-19 can be analyzed better using radiological image data [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there exists efficient full-custom CNN as presented by Pasa et al [39]. In this work, the proposed CNN is compared with some of the state-of-the-art methods that use TL techniques [40][41][42] to obtain better results.…”
Section: Transfer Learning and Chest Diseasesmentioning
confidence: 99%